EFFICIENT FINITE IMPULSE RESPONSE FILTER ARCHITECTURE USING MULTIPLE CONSTANT MULTIPLICATION AND COMMON SUB-EXPRESSION ELIMINATION TECHNIQUES - Shukla, Bhargav; Beulet, Augusta Sophy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
This paper introduces the computationally efficient, low power, high-speed partial reconfigurable finite impulse response (FIR) filter design using multiple constant multiplication technique (MCM). The complexity of many digital signal processing (DSP) systems is reduced by MCM operation. For the better performance of DSP systems, MCM operation is not sufficient. To get better results, some other operations are used with MCM. That's why, this paper introduces a common sub-expression elimination operation of FIR filter design can be solved by decreasing the number of operators. Using these techniques shows the efficiency by reducing area when compared to previously used algorithms designed.